2017
DOI: 10.1097/md.0000000000006910
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status after living donor hepatectomy

Abstract: Donor safety and preservation of donor health after living liver donation are of paramount importance. In addition, the preoperative mental state of a donor is an important factor in determining the psychological impact of donor hepatectomy. Thus, we aimed to explore the mental health status of living liver donors after hepatectomy. We enrolled 60 donors who were scheduled to undergo living donor hepatectomy during the period January 2014 to March 2015 at a single medical center. Mental health status was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In LDLT donors, age and sex, relationship with recipient, ambivalence and motivation to be LDLT donor, feeling for donation, and hospitalization have all also been reported to be associated with psychiatric complications [8,25]. Our observations were consistent with previous reports that suggested that the development of postoperative psychiatric complications was associated with postoperative physical complications [5,6,26,27]. As such, it seems to be important to minimize physiological complications to prevent the development of psychiatric complications in LDLT donors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In LDLT donors, age and sex, relationship with recipient, ambivalence and motivation to be LDLT donor, feeling for donation, and hospitalization have all also been reported to be associated with psychiatric complications [8,25]. Our observations were consistent with previous reports that suggested that the development of postoperative psychiatric complications was associated with postoperative physical complications [5,6,26,27]. As such, it seems to be important to minimize physiological complications to prevent the development of psychiatric complications in LDLT donors.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, approximately 1-10% of LDLT donors have been reported to develop psychiatric complications after donor surgery [5][6][7][8][9]. Interestingly, in many existing studies, it is unclear whether psychiatric complications were diagnosed and treated by a psychiatrist [5,6,8]. Moreover, little is discussed about the long-term outcomes of LDLT donors who develop psychiatric complications.…”
Section: Introductionmentioning
confidence: 99%
“…Though donors were informed about postoperative pain, onethird of them reported that post-procedure pain was greater than anticipated in the immediate postoperative period (37). Our clinical experience also matches up with this.…”
Section: Discussionsupporting
confidence: 70%
“…Although LDLT has helped to resolve the problems of many patients, donors themselves gain no medical benefits, but incur the risks of surgical complications, sometimes with negative psychosocial consequences. Reports have shown that 40% of the living liver donors report psychological distress after surgery (12,37,(43)(44)(45). Our experience shows that donor complications and negative recipient outcomes are major causes of psychological distress.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation